The cytosolic carboxypeptidases CCP2 and CCP3 catalyze posttranslational removal of acidic amino acids - Tort, Olivia (2018)
The posttranslational modification of carboxy-terminal tails of tubulin plays an important role in the regulation of the microtubule cytoskeleton. Enzymes responsible for deglutamylating tubulin have been discovered within a novel family of mammalian cytosolic carboxypeptidases. The discovery of these enzymes also revealed the existence of a range of other substrates that are enzymatically deglutamylated. Only four of six mammalian cytosolic carboxypeptidases had been enzymatically characterized. Here we complete the functional characterization of this protein family by demonstrating that CCP2 and CCP3 are deglutamylases, with CCP3 being able to hydrolyze aspartic acids with similar efficiency. Deaspartylation is a novel posttranslational modification that could, in conjunction with deglutamylation, broaden the range of potential substrates that undergo carboxy-terminal processing. In addition, we show that CCP2 and CCP3 are highly regulated proteins confined to ciliated tissues. The characterization of two novel enzymes for carboxy-terminal protein modification provides novel insights into the broadness of this barely studied process.